Congenital Zika Virus Infection in Immunocompetent Mice Causes Postnatal Growth Impediment and Neurobehavioral Deficits - Paul, Amber M.; Acharya, Dhiraj; Neupane, Biswas; Thompson, E. Ashely; Gonzalez-Fernandez, Gabriel; Copeland, Katherine M.; Garrett, Me’Lanae; Liu, Haibei; Lopez, Mariper E.; de Cruz, Matthew; Flynt, Alex; Liao, Jun; et al. (Frontiers in Microbiology, 2018)
A small percentage of babies born to Zika virus (ZIKV)-infected mothers manifest severe defects at birth, including microcephaly. Among those who appeared healthy at birth, there are increasing reports of postnatal growth or developmental defects. However, the impact of congenital ZIKV infection in postnatal development is poorly understood. Here, we report that a mild congenital ZIKV-infection in pups born to immunocompetent pregnant mice did not display apparent defects at birth, but manifested postnatal growth impediments and neurobehavioral deficits, which include reduced locomotor and cognitive deficits that persisted into adulthood. We found that the brains of these pups were smaller, had a thinner cortical layer 1, displayed increased astrogliosis, decreased expression of microcephaly- and neuron development- related genes, and increased pathology as compared to mock-infected controls. In summary, our results showed that even a mild congenital ZIKV infection in immunocompetent mice could lead to postnatal deficits, providing definitive experimental evidence for a necessity to closely monitor postnatal growth and development of presumably healthy human infants, whose mothers were exposed to ZIKV infection during pregnancy.